Molecular Detection of Nosema spp. in Honey in Bulgaria - Delka Salkova; Rositsa Shumkova; Ralitsa Balkanska; Nadezhda Palova; Boyko Neov; Georgi Radoslavov; Peter Hristov (Veterinary Sciences, 2021)
Environmental DNA (eDNA) analysis is related to screening genetic material of various organisms in environmental samples. Honey represents a natural source of exogenous DNA, which allows for the detection of different honey bee pathogens and parasites. In the present study, we extracted DNA from 20 honey samples from different regions in Bulgaria and tested for the presence of DNA of the ectoparasitic mite Varroa destructor, as well as Nosema apis and Nosema ceranae. Only Nosema ceranae was detected, showing up in 30% of all samples, which confirms the widespread prevalence of this pathogen. All positive samples were found in plain regions of the country, while this pathogen was not detected in mountainous parts. None of the samples gave positive amplifications for the Nosema apis and Varroa mite. The obtained results from this study confirm previous observations that eDNA contained in honey is a potent source for effective biomonitoring of actual diseases in the honey bee.